2023
DOI: 10.1186/s12935-023-02876-z
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic utility of preoperative neutrophil-to-lymphocyte ratio (NLR) in patients with colorectal liver metastasis: a systematic review and meta-analysis

Abstract: The neutrophil-to-lymphocyte ratio is used to reflect body's inflammatory status with prognostic value in different cancers. We aimed to investigate the influence of preoperative NLR in the prognosis of CRLM patients receiving surgery using meta-analysis. Data in Cochrane Library, PubMed, Embase, and Web of Science databases created before October 2022 were recruited. Meta-analysis was carried out with RevMan 5.3 and Stata16 software, and the primary outcome indicators included overall survival (OS), and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…It was found that tumor-infiltrating lymphocyte counts are associated with peculiar gene expression patterns and bear prognostic information in ovarian cancer [ 37 ]. The meta-analysis showed that preoperative neutrophil-to-lymphocyte ratio is an independent risk factor for poor prognosis in patients with colorectal liver metastasis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that tumor-infiltrating lymphocyte counts are associated with peculiar gene expression patterns and bear prognostic information in ovarian cancer [ 37 ]. The meta-analysis showed that preoperative neutrophil-to-lymphocyte ratio is an independent risk factor for poor prognosis in patients with colorectal liver metastasis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, as a mature inflammation-related marker, NLR has been widely confirmed to predict short- and long-term adverse outcomes in haematologic and solid tumours [ 35 ]. The underlying mechanism is that neutrophils provide a favourable microenvironment for tumour cell proliferation and promote tumour cell progression and invasion [ 36 ]. Conversely, a reduction in lymphocyte numbers suppresses the immune response to cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio (NLR) is known to increase in many types of tumors including sarcoma, and is closely related to a shorter OS, disease-free survival, or progression-free survival [64][65][66][67][68] . The high NLR has been considered a biomarker of poor clinical outcomes in gastric, triple-negative breast, colorectal, pancreatic, thyroid, and ovarian cancers and soft tissue sarcoma [69][70][71][72][73][74][75][76] . Moreover, the results of a recent study about sarcomas indicate that high NLR may be associated with chemoresistance [77] .…”
Section: Clinical Value Of Neutrophilsmentioning
confidence: 99%